Impaired reward processing in the human prefrontal cortex distinguishes between persistent and remittent attention deficit hyperactivity disorder. Issue 11 (19th August 2015) - Wetterling, Friedrich; McCarthy, Hazel; Tozzi, Leonardo; Skokauskas, Norbert; O'Doherty, John P.; Mulligan, Aisling; Meaney, James; Fagan, Andrew J.; Gill, Michael; Frodl, Thomas
Abstract Symptoms of attention deficit hyperactivity disorder (ADHD) in children often persist into adulthood and can lead to severe antisocial behavior. However, to‐date it remains unclear whether neuro‐functional abnormalities cause ADHD, which in turn can then provide a marker of persistent ADHD. Using event‐related functional magnetic resonance imaging (fMRI), we measured blood oxygenation level dependent (BOLD) signal changes in subjects during a reversal learning task in which choice of the correct stimulus led to a probabilistically determined 'monetary' reward or punishment. Participants were diagnosed with ADHD during their childhood (N = 32) and were paired with age, gender, and education matched healthy controls (N = 32). Reassessment of the ADHD group as adults resulted in a split between either persistent (persisters, N = 17) or remitted ADHDs (remitters, N = 15). All three groups showed significantly decreased activation in the medial prefrontal cortex (PFC) and the left striatum during punished correct responses, however only remitters and controls presented significant psycho‐physiological interaction between these fronto‐striatal reward and outcome valence networks. Comparing persisters to remitters and controls showed significantly inverted responses to punishment (P < 0.05, family‐wise error corrected) in left PFC region. Interestingly, the decreased activation shown after punishment was located in different areas of the PFC for remitters compared with controls, suggesting that remitters might have learned compensation strategies to overcome their ADHD symptoms. Thus, fMRI helps understanding the neuro‐functional basis of ADHD related behavior differences and differentiates between persistent and remittent ADHD. Hum Brain Mapp 36:4648–4663, 2015. © 2015 Wiley Periodicals, Inc.